Analisis Efisiensi Bank Umum Syariah Di Indonesia DenganMenggunakan Data Evelopment Analysis (DEA)(Studi pada Bank BNI Syariah, Bank Mega Syariah, Bank Muamalat, Bank SyariahMandiri, Bank BRI Syariah, Bank BCA Syariah, Bank Bukopin Syariah Tahun 2015) - Muftias, Anisa; , Dr. Imron Rosyadi, M.Ag; , Didit Purnomo, SE., M.Si (2017)
Bank Syariah (Islamic Bank) is a part of banking system that has a big role in encouraging the national economic growth. This research aims to know the efficiency level of Islamic Common Bank in Indonesia in the period of 2015 by using the method of Data Envelopment Analysis (DEA). By using the secondary data obtained from the three-month financial report of 7 Islamic Common Bank in Indonesia which had been published in the official site of the Financial Service Authority www.ojk.go.id. To ease the research, the researcher used the software of DEAP version 2.1. The measurement used the multi input and output to know the comparison of performance of Islamic Common Bank. An Islamic Common Bank can be said as having an efficient performance if it has an efficiency score of 1 or 100% and said as less and less efficient (inefficient) if the score approaches 0. This research used 7 samples of Islamic Common Bank in Indonesia, they are: Bank BNI Syariah, Bank Mega Syariah, Bank Muamalat, Bank Syariah Mandiri, Bank BRI Syariah, Bank BCA Syariah, and Bank Bukopin Syariah during the first three-month up to the fourth three-month in 2015. Inputs which were used were the saving and the operational cost, meanwhile, the outputs which were used were the financing and other operational incomes. The results of analysis using DEA revealed that there are only two efficient banks during the period of 2015, they are: Bank Muamalat and Bank Bukopin Syariah. Meanwhile, other five banks have not been completely efficient.